Teachers’ expectations and EFL differentiated planning proposal for a 4th grade student with autism. - Falcones Reinoso, Byron Xavier (2017)
This Project was conducted in order to gather information about the lowered expectations perception that the EFL elementary school teachers form Unidad Educativa Bilingüe “Sir Thomas More” have upon a student with moderate autism spectrum disorder from 4th grade. First, a bibliographical research was carried in other to explore the rights in the Ecuadorian legal framework (LOEI) and its implication with inclusion students.There were studied theories about autism, gatheredthe concepts, the prevalence, causes, and the features presented in a child with autism. Furthermore, pedagogical and inclusion strategies theories were gathered to have a vast Knowledge in order to conduct the proposal. Moreover, there was found the relationship between child with autism, and the EFL environment. It was also found how teachers’ expectations can affect students’ academic performance, so that it was collected information about differentiation and some strategies. Second, the methodology designed used in this studywas mixed methods. In order to gather data from the teacher’s expectations upon the inclusive student. It was also used an observation sheet in order to gather information about the content, the assessment and the social classroom interaction that the student presents when she is immersed in the classroom. Third, according to the data analysis it was suggested a proposal under a differentiated methodology.